Necrotizing Enterocolitis: LPS/TLR4-Induced Crosstalk Between Canonical TGF-β/Wnt/β-Catenin Pathways and PPARγ - Gomart, Alexia; Vallée, Alexandre; Lecarpentier, Yves (Frontiers in Pediatrics, 2021)
Necrotizing enterocolitis (NEC) represents one of the major causes of morbidity and mortality in premature infants. Several recent studies, however, have contributed to a better understanding of the pathophysiology of this dreadful disease. Numerous intracellular pathways play a key role in NEC, namely: bacterial lipopolysaccharide (LPS), LPS toll-like receptor 4 (TLR4), canonical Wnt/-catenin signaling and PPAR. In a large number of pathologies, canonical Wnt/-catenin signaling and PPAR operate in opposition to one another, so that when one of the two pathways is overexpressed the other is downregulated and vice-versa. In NEC, activation of TLR4 by LPS leads to downregulation of the canonical Wnt/-catenin signaling and upregulation of PPAR. This review aims to shed light on the complex intracellular mechanisms involved this pathophysiological profile by examining additional pathways such as the GSK-3, NF-B, TGF-/Smads and PI3K-Akt pathways.